Profiling the performance of P4080DS - Zheng, Zhipeng (2015)
This report presents the method to test and profile the performance of P4080, an eight-core processor by Freescale, using two approaches, the hypervisor approach and the hardware approach. The focus is to explore the cache partitioning and memory partitioning functions of P4080DS and how this could affect the performance in terms of execution time and cache hit ratio. This report contains detailed procedures of both hypervisor approach and hardware approach. The hypervisor approach created 8 partitions by modifying the device tree of hypervisor. Similarly, the hardware approach created 8 partitions by configuring the internal register sets. With partitioned system, 4 sets of experiments were conducted to test and compare the performance of P4080DS in different situations. The results suggested that the performance of individual partition is independent of number of cores running simultaneously. The results also showed that the measured hit ratios of individual partition match with the theoretical values.